Implementation of the Religious Literacy Program as an Effort to Strengthen Multicultural Education at SMPN 15 Mataram - Oktapianti; Hasmika Auliya Putri; Iqlima Septia Irdani; Fatmah Putri Anggraini; Muhammad Khozin Arif Amrullah; Sawaludin (al-Afkar, Journal For Islamic Studies, 2026)
The religious literacy program at SMPN 15 Mataram is one of the programs that is considered strategic in improving students' multicultural education. This program is designed to provide an in-depth understanding of religious values through various activities, such as reading and studying holy books, taking part in religious studies, and carrying out social activities based on religious values. However, in its implementation, religious literacy programs do not always run smoothly. There are various challenges faced in implementing this program. The results of the qualitative research method emphasize descriptive results, the data collection techniques used in this research are non-test techniques consisting of questionnaires, observations and interviews. This research was conducted on November 12 2024. This research focuses on the implementation of religious literacy programs as an effort to strengthen multicultural education. In the context of multicultural education, this program instills positive values such as religious values, discipline values, responsibility values, courtesy values, and tolerance values.